Association of LDL‐C/HDL‐C Ratio With Hyperuricemia: A National Cohort Study - Yanyu Zhang; Xiaoyi Liu; Deyun Luo; Bingli Chen; Chenyi Lai; Chenyu He; Luo Yan; Haifeng Ding; Shiyang Li (Clinical and Translational Science)
ABSTRACT Hyperuricemia (HUA) is a metabolic abnormality syndrome caused by disorders of purine metabolism. This study aimed to investigate the predictive value of the low‐density lipoprotein cholesterol to high‐density lipoprotein cholesterol ratio (LHR) for the risk of developing HUA. We extracted data from the China Health and Retirement Longitudinal Study (CHARLS) database from 2011 to 2016. Multivariable logistic regression, restricted cubic splines (RCSs) analysis, and linear correlation analysis were conducted to evaluate the association between LHR and risk of developing HUA. Subgroup analyses and interaction tests were also performed. A higher LHR was associated with an increased incidence of HUA (7.8% vs. 9.9% vs. 13.9, p < 0.001). The LHR was also higher in the HUA group compared to the non‐HUA group (2.64 ± 1.07 vs. 2.40 ± 0.91, p < 0.001). When assessed as a continuous variable, LHR was independently associated with the risk of HUA (OR = 1.27, 95% CI = 1.16–1.39, p < 0.001). The risk of developing HUA was significantly higher among individuals with the highest LHR subgroup than those with the lowest LHR subgroup (OR = 1.81, 95% CI = 1.47–2.23, p < 0.001). RCS analysis revealed a significant nonlinear association between an increased LHR and a higher risk of developing HUA. The predictive abilities of LHR for HUA were 0.577. The composite variable comprising LHR and other traditional risk factors could significantly enhance the ability to predict HUA (C statistic = 0.677). In conclusion, a higher LHR was associated with an increased risk of developing HUA. Further studies on LHR could be beneficial for preventing and treating HUA.